ANALYSIS OF A LOW PROTEIN DIET - Otajonov I. O.; Ochilov J. T.; Gayibnazarov S. S.; Karaeva M. M. (Web of Journals Publishing, 2025)
Recommendation of a low-protein diet for patients with chronic kidney disease in the pre-dialysis period had a clear positive effect in terms of slowing down the progression, improving the metabolic parameters and nutritional status of patients. In the daily diet, protein is 0,6-0,7 g per 1 kg of body weight of patients, the main "suppliers" of energy are fats and carbohydrates, which fully satisfy the daily energy needs of patients.
Keywords: Chronic kidney disease, patients, low-protein diet, ration.